2023
DOI: 10.3390/electronics12030647
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Resource Management for 6G Heterogeneous Networks: Current Research, Future Trends, and Challenges

Abstract: The sixth generation (6G) mobile communication system is expected to meet the different service needs of modern communication scenarios. Heterogeneous networks (HetNets) have received a lot of attention in recent years due to their potential as a novel structure for evolutionary networks. When compared to homogeneous networks, HetNets provide more potential for spatial spectrum reuse and higher quality of service (QoS). However, effective resource management (RM) solutions are essential to prevent interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 161 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…In Fig. 7, the average data rate is demonstrated for various number of channels (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The proposed method clearly achieves a higher average data rate in the proposed scenario S2 when compared to proposed scenario S1, proposed scenario S3, and benchmark algorithms.…”
Section: Table I Simulation Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…In Fig. 7, the average data rate is demonstrated for various number of channels (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The proposed method clearly achieves a higher average data rate in the proposed scenario S2 when compared to proposed scenario S1, proposed scenario S3, and benchmark algorithms.…”
Section: Table I Simulation Parametersmentioning
confidence: 98%
“…Additionally, the gNB must choose the optimal D2D mode in order to maximize the data rate [12]. In terms of channel allocation, D2D communication may use either the licensed spectrum or the unlicensed spectrum to establish direct links, often known as the inband and the outband D2D communications [13], [14] respectively. There are two classifications for inband D2D communication: underlay and overlay.…”
Section: Introductionmentioning
confidence: 99%
“…Alhashimi et al suggested combining training and optimizing methods to solve mixedinteger concave programming problems in satellite RRM at satellite communications [7]. The intricate issue is divided into two categorization jobs and a power control challenge.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, resource optimization is a crucial question that should not be left in developing the 6G IoT system. [9]. The existing resource optimization technologies cannot match the QoS demands in 6G IoT networks [10].…”
Section: Introductionmentioning
confidence: 99%